2014
DOI: 10.1007/s00256-014-1818-5
|View full text |Cite
|
Sign up to set email alerts
|

Hip imaging of avascular necrosis at 7 Tesla compared with 3 Tesla

Abstract: 7-T hip MRI showed comparable results in hip joint imaging compared with 3 T with slight advantages in contrast detail (cartilage defects) and fluid detection at 7 T when accepting image degradation medially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…However, further research is needed to discover the full potential of this technique which could be applied in pre-collapse stages. In two different papers, Theysohn et al(55,56) analyzed 7T advantages and compared it to 3T magnets. Images obtained using a home-made coil, were judged according to a 4 point scale.…”
mentioning
confidence: 99%
“…However, further research is needed to discover the full potential of this technique which could be applied in pre-collapse stages. In two different papers, Theysohn et al(55,56) analyzed 7T advantages and compared it to 3T magnets. Images obtained using a home-made coil, were judged according to a 4 point scale.…”
mentioning
confidence: 99%
“…Sundberg et al [31] reported that 3.0-T MRI was as effective as 1.5-T d-MRA at detecting labral tears in all subjects. High-resolution T2*-weighted imaging, such as MERGE, is used to obtain detailed anatomical information on the cartilage or labrum in the hip and other joints [32]. Furthermore, spinal imaging with MERGE has shown high sensitivity for depicting edematous and hemorrhagic changes [33] as well as excellent depiction of soft tissue structures such as intervertebral discs and the ligamentum flavum in degenerative diseases of the cervical spine [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study, Theysohn et al . presented the first comparison study between 3 and 7 T in 13 patients suffering from avascular necrosis of the femoral head, treated using advanced core decompression. Two radiologists evaluated the MR protocol consisting of multi‐echo data image combination (MEDIC), dual‐echo steady‐state (DESS), PD/T2w TSE, T1w TSE and short‐time inversion recovery (STIR), in which the sequence parameters and resolution were kept identical for 3 and 7 T. The assessed items were subjective image quality, soft tissue contrasts, B 1 homogeneity and depiction of imaging abnormalities of the femoral heads.…”
Section: Whole‐body Imaging – Clinical Comparison Studies Between 3 Tmentioning
confidence: 99%